Correlative models for perovskites with rock salt B‐site ordering. Issue 1 (30th July 2019) - Smith, Evan; Adams, Claire; Ubic, Rick
Abstract: Empirically derived predictive models describing synthesis‐structure relationships have the potential to significantly improve and guide future research in a more cost‐effective and timely manner; however, few of these models exist for cation ordering in perovskites. In this study, four compositions within the AZn0.5 Ti0.5 O3 system (A = Nd, Sm, Nd0.5 La0.5, Nd0.5 Gd0.5 ) were synthesized using a conventional solid‐state mixed‐oxide method. X‐ray diffraction data show evidence of long‐range 1:1 rock salt cation ordering on the B site for all compositions. Additional data for other rock salt B‐site ordered compositions were mined from literature. Correlative models for the B‐site shrinkage (Δ r B ) have been derived for each B‐site ordered system, and a general model has been developed for rock salt B‐site ordering from these specific models. This general model allows for the prediction of the room‐temperature volume shrinkage resulting from rock salt B‐site ordering using only published ionic radii data.